Isolation and Phenotypic Characterization of Cancer Stem Like Cells from Nasopharyngeal Carcinoma - Wang, Y.; Zhang, G.-H.; Li, S.-L. (Drug Research, 2015)
Introduction: Recent studies reported that cancer stem cells (CSCs) are responsible for treatment failure and tumor recurrence. CSCs have been isolated and characterized in several solid tumors. However, the information regarding the CSCs from nasopharyngeal carcinoma (NPC) is very less. Therefore, in the current study we aimed to isolate and characterize the cancer stem like SP cells from NPC.Methods: We have used FACS based Hoechst 33342 dye exclusion technique to identify the cancer stem like SP cells from NPC. The FACS sorted SP cells are further subjected to drug resistance assay, clonogenic formation assay and immunocytochemistry analysis for the expression of CD44 and ABCG2.Results: We have identified 3.9% of cancer stem like SP cells from NPC. Upon treatment with verapamil, the percentage of SP cells was reduced to 0.9%. The FACS sorted SP cells showed enhanced expression of CD44 and ABCG2. Further, these SP cells are highly resistant to multi-drugs and high potent of sphere formation when compared to the non-SP cells.Conclusions: Our data clearly suggest that presence of cancer stem like SP cells from nasopharyngeal carcinoma might responsible for chemotherapeutic drug resistance, tumor recurrence and invasion.
Keywords: chemotherapy; cancer stem cells; tumor recurrence; side population cells; ABC transporters